2011
DOI: 10.3801/iafss.fss.10-681
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on Burning Rate, Vertical Velocity and Radiation of Medium-Scale Fire Whirls

Abstract: Fire whirls are often reported in forest and urban fires with devastating damage to life and property. This work conducted experiments using a medium-scale facility to study the initiation mechanism, the vertical velocity and radiative heat transfer of fire whirls. Heptane was used as the fuel in the experiments. The variations of burning rates versus time indicate that the drag force on the root of the flame plays an important role in the initiation and decay of a fire whirl. Analyses show that the pressure d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…However, this is not the case for fire whirls, as Zhou et al (2011) argued that both buoyant plume theory and the circulation-induced vortex should be included in the dimensional analysis. According to Zhou et al (2011), Fr is approximately ( / gz 3 ) η , where η is found to be 0.22 through the continuous flame region and 0.77 through the plume. However, this scaling seems to be inappropriate because the circulation in the free vortex region is typically constant along the vertical direction (Lei et al 2011.…”
Section: Circulationmentioning
confidence: 98%
See 4 more Smart Citations
“…However, this is not the case for fire whirls, as Zhou et al (2011) argued that both buoyant plume theory and the circulation-induced vortex should be included in the dimensional analysis. According to Zhou et al (2011), Fr is approximately ( / gz 3 ) η , where η is found to be 0.22 through the continuous flame region and 0.77 through the plume. However, this scaling seems to be inappropriate because the circulation in the free vortex region is typically constant along the vertical direction (Lei et al 2011.…”
Section: Circulationmentioning
confidence: 98%
“…Following the discussion above, heat transfer at the fuel surface was thought to increase significantly due to the flow structure (presence of swirl), effectively increasing the heat transfer coefficient for fire whirls (Muraszew et al 1979). In larger fires, the radiative heat feedback fraction was found to increase for fire whirls compared to that of pool fires (Zhou et al 2011). However, Snegirev et al (2004) found that this fraction decreases slightly with circulation.…”
Section: Boundary Layer and Burning Ratementioning
confidence: 99%
See 3 more Smart Citations